Skolen for livet. Anmeldelse af K. E. Bugges disputats. - Thyssen, A. Pontoppidan (Grundtvig-Studier, 1965)
The School for Life By A. Pontoppidan Thyssen. The present treatise is a critical contribution to the debate on a thesis which was defended by K. E. Bugge, June 8, 1965, at the University of Copenhagen. This thesis deals with Grundtvig’s views on education and falls into three main parts. The first part purports to show how, chiefly under the influence of Romantic ideas, Grundtvig’s earliest development led him to an idealistic type of educational theory which made the development of personality the aim of any kind of education. The second part seeks to demonstrate that afterwards, 1808-30, he gradually developed away from this standpoint; and finally the third part describes Grundtvig’s real educational endeavours in the 1830’s and 40’s as a process of clarification consolidating the difference between Grundtvig and earlier and contemporary educational theory which attached special importance to the development and education of personality. In his criticism the author emphasizes the value of Bugge’s work. As we have seen it aims at giving a connected account of Grundtvig’s educational development, and its thorough treatment of Grundtvig’s early thoughts on education deserves special mention. Besides, Bugge has sought, through a comprehensive illustration of Grundtvig’s sources of inspiration and background in contemporary educational theory, to disengage him from the isolation so often surrounding his thoughts. He has also, and rightly, pointed to the difference between Grundtvig’s view and Romantic-Idealistic educational theory, but at this point the question is asked whether, in his way of presenting the problem, Bugge has got to the heart of the matter. The objections raised centre on this point in particular. Against Bugge’s chief point of view stress is laid on the connection between Grundtvig’s educational ideas and his general attitude as a critic of the age which is in opposition less to Romanticism than to the materialistic outlook of the Enlightenment. Already in the writings of the Langeland period this attitude towards the Enlightenment is there and should be considered more important than the influence from educational theory concentrating on the development of personality. The following period, 1808-30, should rather be looked upon as an elaboration of Grundtvig’s “ culture criticism” than as an increasing dissociation from the Langeland period. After the crisis of 1810-11 Grundtvig, the Christian, departs from Romantic religious idealism, but the structure of his views on education and “ Aandsudvikling” (spiritual development) is still determined by Romanticism. Christianity is now the foundation and chief expression of spiritual life, which also, however, expresses itself through poetry, “ Videnskabelighed” and national achievements. The more detailed exposition of these ideas in the Danne-Virke period is also, more or less, inspired by Romanticism. Grundtvig’s basic attitude is still that of the critic, and the chief object of attack is the materialism and “ falske Oplysning” (false enlightenment) of the age. The same is largely true of the Folk High-school writings of the 1830’s and 40’s. Here Bugge has demonstrated that Grundtvig’s ideas about school teaching develop through three phases, connected with the years 1832, 1834, and 1836 (-38), but attached little importance to the strong controversy which has left its mark on them all: in 1832 (Nordens Mythologi) against “den Romersk-Italienske Videnskabelighed” (Romano-Italian learning), where reason seeks to rule over life, i. e. the outlook of the Enlightenment which Grundtvig now traces back to the Renaissance and ancient Rome; in 1834 (esp. “Den danske Stats-Kirke upartisk betragtet” ) against the socially subversive wilfulness produced by “ Forstandstiden” (the age of reason), and in 1836-38 (the first school writings proper) also against “ den mathematiske Realskole” representing in Grundtvig’s opinion the same arid “Bogormevæsen” (book-worm attitude) as Latin education. Thus the study of Grundtvig’s polemical situation is a necessary condition of understanding the positive content of his views on school teaching, which has also received a rather summary treatment in Bugge’s thesis. But these objections do not detract from the value of the work presented. It has laid a sound foundation for all future examinations within the field.